MASKING EFFECT OF PEPPERMINT FRAGRANCE STIMULUS ON CAR HORN SOUND STIMULUS WHILE DRIVING IN A GRAPHIC DRIVING SIMULATOR - Cheol Kee Min, Pil Kee Min, Tsutomu Fujinami, Hyung-Sik Kim, Jun Bin Ko (International Journal of Advanced Science and Technology, 2019)
In this study, autonomic nervous system responses including heart rate variability (HRV) and galvanic skin response (GSR) were observed to examine the masking effect of peppermint fragrance stimulus on car horn sound stimulus in a graphic driving simulator. When the pre-experiment and post-experiment measurements for GSR were compared in car horn sound stimulus experiment (1) (p<0.01), experiment (2) (p<0.05), and experiment (3) (p<0.01), driving experiment (2) (p<0.01) and experiment (3) (p<0.01), and peppermint fragrance stimulus experiment (3) (p<0.05), the measurements of all the experiments increased with significant differences after the experiment. This suggests that when the car horn sound stimulus was presented, the sympathetic nervous system was activated and aroused. With respect to the LF/HF ratio of the HRV, when a car horn sound stimulus was presented during driving, it showed different values depending on the presentation of peppermint fragrance. When the car horn sound stimulus was compared between before and after presenting peppermint fragrance while driving, it decreased with a significant difference (p<0.05). In conclusion, the arousal level by the car horn sound stimulus while driving decreased due to the peppermint fragrance stimulus. Therefore, the peppermint fragrance stimulus is considered to have a masking effect on the car horn sound stimulus.